2009
DOI: 10.4315/0362-028x-72.3.631
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatments for Killing Escherichia coli O157:H7 on Alfalfa, Radish, Broccoli, and Mung Bean Seeds

Abstract: In this study, the effectiveness of prolonged dry-heat treatment (50 degrees C) alone or in combination with chemical treatments (1% oxalic acid, 0.03% phytic acid, 50% ethanol, electrolyzed acidic water, and electrolyzed alkaline water) in eliminating Escherichia coli O157:H7 on laboratory-inoculated alfalfa, radish, broccoli, and mung bean seeds was compared with that of dry-heat treatment in combination with irradiation treatment. Dry-heat treatment for 17 or 24 h alone could reduce E. coli O157:H7 numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…To achieve greater reductions in numbers of food-borne pathogens, sequential or simultaneous treatments with chlorine-based sanitizers, organic acids, heat, high pressure, and irradiation have been evaluated (6,13,17,21,23,31). Although most studies using multiple treatments have been shown to result in greater reductions in pathogens than those using a single treatment, with some exceptions (3,4), elimination of pathogens without decreasing the germination rate of seeds has been difficult. Bari et al (4) reported that E. coli O157:H7 was eliminated from alfalfa, mung bean, and radish seeds without decreasing the germination rate and yield by applying dry heat (50°C for 1 h) and irradiation (2.5 kGy).…”
mentioning
confidence: 99%
“…To achieve greater reductions in numbers of food-borne pathogens, sequential or simultaneous treatments with chlorine-based sanitizers, organic acids, heat, high pressure, and irradiation have been evaluated (6,13,17,21,23,31). Although most studies using multiple treatments have been shown to result in greater reductions in pathogens than those using a single treatment, with some exceptions (3,4), elimination of pathogens without decreasing the germination rate of seeds has been difficult. Bari et al (4) reported that E. coli O157:H7 was eliminated from alfalfa, mung bean, and radish seeds without decreasing the germination rate and yield by applying dry heat (50°C for 1 h) and irradiation (2.5 kGy).…”
mentioning
confidence: 99%
“…Many researchers have published the methods how sprouts could be decontaminated and secure to eat (BAri et al, 2008(BAri et al, , 2009WAje et al, 2009;Nei et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The bacteria which can be present there (44) are not accessible to various chemical disinfectants such as, e.g., hypochlorite, since these disinfectants are not able to penetrate the seed coat (45)(46)(47). The extent to which aerated steam can be applied to eliminate bacterial loads not only on the outer seed surface but also in the inner parts of the seed needs to be studied in future work.…”
Section: Discussionmentioning
confidence: 99%